DON affects the proliferation of zebrafish PAC2 fibroblasts by binding to ribosomes, reducing DNA replication, arresting the cell cycle and interfering with mitosis - Huimin Duan; Yongsheng Tian; Zhentong Li; Aizhong Han (Ecotoxicology and Environmental Safety)
Deoxynivalenol (DON) is a type of mycotoxin that widely contaminates aquatic feed. Although the detrimental effects of DON on fish have been investigated, the specific impacts of DON on the proliferation of zebrafish PAC2 fibroblasts remain unclear. In this study, it was found that DON significantly suppressed the proliferation of zebrafish PAC2 fibroblasts in a dose-dependent manner. Through RNA-seq, GSEA, molecular docking and immunofluorescence analysis, we discovered that genes related to the ribosome, ECM and DNA replication were significantly down-regulated. Interestingly, we verified that DON binds to ribosomes and DON exposure could interfere with the mitosis of zebrafish embryonic fibroblasts and arrest the cell cycle. Additionally, we found that DON treatment activated autophagy-animals and mitophagy-animals signaling pathway. This study might offer valuable perspectives on the mechanisms beneath DON toxicity in zebrafish PAC2 fibroblasts.